2005
DOI: 10.1016/j.febslet.2005.03.062
|View full text |Cite
|
Sign up to set email alerts
|

The FAXWXXT motif in the carboxyl terminus of Vibrio mimicus metalloprotease is involved in binding to collagen

Abstract: We have shown previously that the C-terminal region of the extracellular metalloprotease of Vibrio mimicus (VMC) is essential for collagenase activity. Here, we demonstrate that deletion of 100 amino acids, but not 67 amino acids, from the C-terminus of the intact VMC protein (VMC61) abolished the collagenase activity. The intervening 33-amino acid region contains a repeated FAXWXXT motif that is essential for insoluble type I collagen binding; the isolated 33-amino acid peptide bound to insoluble type I colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…In addition, two FAXWXXT motifs, FDQWAQS and FSAWLDT (conserved residues are in boldface), which are implicated in collagen binding (32), and two bacterial prepeptidase C-terminal (PPC) domains also were identified at amino acids 537 to 543, 555 to 561, 612 to 686, and 731 to 804, respectively. A comparison of the amino acid sequences of class II metalloproteases in different Vibrio species showed that VC1650 displays the highest similarity (over 70%) to the 61-kDa collagenase VMC from V. mimicus and 63-kDa PrtVp protease (VPPRT) from V. parahaemolyticus 93 (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two FAXWXXT motifs, FDQWAQS and FSAWLDT (conserved residues are in boldface), which are implicated in collagen binding (32), and two bacterial prepeptidase C-terminal (PPC) domains also were identified at amino acids 537 to 543, 555 to 561, 612 to 686, and 731 to 804, respectively. A comparison of the amino acid sequences of class II metalloproteases in different Vibrio species showed that VC1650 displays the highest similarity (over 70%) to the 61-kDa collagenase VMC from V. mimicus and 63-kDa PrtVp protease (VPPRT) from V. parahaemolyticus 93 (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…Very limited information is available regarding the tertiary structure of the Vibrio collagenases belonging to the M9A subfamily, and the function and biochemical properties of their domains, as well as the physiological importance of the C-terminal processing, remain to be addressed. It can be speculated that the removal of both PPC domains exposes the repeated FAXWXXT motif, which has been implicated in binding to insoluble type I collagen (32), and provides a better interaction with the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the substratebinding domains of bacterial MMPs are much smaller than the substrate-binding domains of mammalian MMPs. It has been demonstrated that ϳ33 amino acids of the Vibrio mimicus metalloprotease C-terminal domain or ϳ100 amino acids of the Clostridium histolyticum metalloprotease C-terminal domain are necessary for substrate binding, compared to ϳ200 amino acid residues for the hemopexin-like domain in mammalian MMPs (17,36). Thus, we hypothesize that the C-terminal amino acid residues are responsible for binding to the BFT substrate.…”
Section: Vol 74 2006 Structure-function Properties Of B Fragilis Tmentioning
confidence: 99%
“…Mammalian MMPs are larger than bacterial MMPs and contain various arrangements of substrate-binding domains, including fibronectin-like and hemopexin domains, in their C-terminal regions (26). Recently, studies have shown that, similar to the C terminus of mammalian MMPs, the C-terminal regions of some bacterial MMPs contain a collagen-binding domain, as shown by loss of collagenase activity after deletion of the C-terminal region (17,18,34). However, the substratebinding domains of bacterial MMPs are much smaller than the substrate-binding domains of mammalian MMPs.…”
Section: Vol 74 2006 Structure-function Properties Of B Fragilis Tmentioning
confidence: 99%
See 1 more Smart Citation